MODEL COOPERATIVE LEARNING DALAM PEMBELAJARAN PENDIDIKAN JASMANI - Ni Komang Putri Wulandari; I Ketut Semarayasa; Luh Putu Tuti Ariani (Universitas Hamzanwadi, 2026)
Physical Education, Sports, and Health (PJOK) instruction in schools still tends to be conventional and teacher-centered, resulting in suboptimal student motivation, active participation, and social skill development. This study aims to examine the application of the Cooperative Learning model in PJOK instruction based on research findings and expert opinions from the past ten years. The method used was a systematic literature review, analyzing 25 national and international scientific articles published between 2015 and 2025, sourced from the Google Scholar, DOAJ, ERIC, ScienceDirect databases, and SINTA-accredited journals. The results of the review indicate that the Cooperative Learning model has a positive impact on the quality of Physical Education and Health (PJOK) instruction, as evidenced by improvements in learning outcomes in the cognitive domain (84% of articles), affective domain (96%), psychomotor domain (88%), learning motivation (92%), active student participation (96%), and social skills such as cooperation, responsibility, and sportsmanship (100% of articles). The conclusion of this study is that the Cooperative Learning model is a relevant and effective learning model to be applied in Physical Education and Health (PJOK) instruction to create an active, collaborative, and student-centered learning environment.